Kesejahteraan Sosial di Kampus Peradaban - DN, Syakhruddin (Universitas Islam Negeri Alauddin Makassar, 2013)
Social work as charity work, helping each other, helping people in distress, is already underway and institutionalized since ancient times based on human values and needs of the social conditions of society at the time as hunters, sailors, and farmers. When Buddhism, Hinduism, Islam and Christianity entered the archipelago, reinforcing the values of mutual help with the values of faith.